John Gower in Manuscripts and Early Printed Books - Driver, Martha W. (Publications of the John Gower Society Ser, 2020)
Frontcover -- Contents -- List of Illustrations -- Acknowledgements -- List of Contributors -- List of Abbreviations -- Introduction -- Part I: In Manuscript -- 1 John Gower's Scribes and Literatim Copying -- 2 Looking for Richard: Finding "Moral Gower" in Oxford, Bodleian Library, MS Hatton 92 -- 3 A State above All Other: The Recensions of Confessio Amantis and the Anthropology of Sovereignty -- 4 What Lies Beneath -- 5 Earthly Gower: Transforming Geographical Texts and Images in the Confessio Amantis and Vox Clamantis Manuscripts -- Paratextual Deviations: The Transmission and Translation of Gower's Confessio Amantis in the Iberian Peninsula -- 7 "Mescreantz," Schism, and the Plight of Constantinople: Evidence for Dating and Reading London, British Library, Additional MS 59495 -- 8 John Shirley and John Gower -- Part II: In Print -- 9 Gower between Manuscript and Print -- 10 Gower from Print to Manuscript: Copying Caxton in Oxford, Bodleian Library, MS Hatton 51 -- 11 A Caxton Confessio: Readers and Users from Westminster to Chapel Hill -- 12 English Poets in Print: Advertising Authorship from Caxton to Berthelette -- 13 In Praise of European Peace: Gower's Verse Epistle in Thynne's 1532 Edition of Chaucer's Workes -- 14 George Campbell Macaulay and the Clarendon Edition of Gower -- Bibliography -- Index.